Open-Set Gait Recognition From Sparse mmWave Radar Point Clouds - Mazzieri, Riccardo; Pegoraro, Jacopo; Rossi, Michele (IEEE sensors journal, 2025)
The adoption of millimeter-wave (mmWave) radar devices for human sensing, particularly gait recognition, has recently gathered significant attention due to their efficiency, resilience to environmental conditions, and privacy-preserving nature. In this work, we tackle the challenging problem of open-set gait recognition (OSGR) from sparse mmWave radar point clouds. Unlike most existing research, which assumes a closed-set scenario, our work considers the more realistic open-set case, where unknown subjects might be present at inference time, and should be correctly recognized by the system. Point clouds are well-suited for edge computing applications with resource constraints, but are more significantly affected by noise and random fluctuations than other representations, like the more common micro-Doppler signature. This is the first work addressing open-set gait recognition with sparse point cloud data. To do so, we propose a novel neural network architecture that combines supervised classification with unsupervised reconstruction of the point clouds, creating a robust, rich, and highly regularized latent space of gait features. To detect unknown subjects at inference time, we introduce a probabilistic novelty detection algorithm that leverages the structured latent space and offers a tunable trade-off between inference speed and prediction accuracy. Along with this article, we release mmGait10 , an original human gait dataset featuring over 2 h of measurements from ten subjects, under varied walking modalities. Extensive experimental results show that our solution attains {24}% average {F}1 -score improvement over state-of-the-art methods adapted for point clouds, across multiple openness levels.